Mga hulwarang kagamitang panturo sa sining ng pakikipagtalastasan sa unang taon sa mga estudyanteng Cebuano sa Iligan City High School - Jabagat, Guadalupe Aguilo 1936- (1976)
This seminar paper was made because of the felt need for instructional materials in Pilipino at the Iligan City High School. The preparation was preceded by a study of related literature on the preparation of instructional materials. These instructional materials are divided into ten lessons to be finished within a grading period. Each lesson contains different activities and practice exercises for the development of the four language skills in language teaching. The writer made use of integrated approach because she believes that the four elements (phonology, vocabulary, structure or grammar and culture) and the four language learning skills (listening, speaking, reading and writing) should not be taught separately.
"Mayo, 1976."
Vita.
Thesis (M.A.T. Pilipino)--University of the Philippines, Diliman.
Keywords: Filipino language -- Study and teaching (Secondary) -- Cebuano speakers; Filipino language -- Study and teaching (Secondary) -- Aids and devices; High school freshmen -- Philippines -- Iligan City (Lanao del Norte); Teaching -- Philippines -- Iligan City (Lanao del Norte) -- Aids and devices